PEDAGOGICAL EDUCATION IN RUSSIA: ANNIVERSARY ISSUE FOR THE 50th ANNIVERSARY OF THE PEDAGOGICAL FACULTY OF NABEREZHNYE CHELNY STATE PEDAGOGICAL UNIVERSITY AND THE 15th ANNIVERSARY OF THE JOURNAL - Timur A. Magsumov (Russian Journal of Education and Psychology)
The special thematic issue of the journal is dedicated to the 50th anniversary of the Pedagogical Faculty of Naberezhnye Chelny State Pedagogical University and the 15th anniversary of the Russian Journal of Education and Psychology.